Tri Pramana-Based Digital Learning Media: Enhancing Students’ Science Learning Outcomes in Elementary Schools - Winangun, I Made Ari (Universitas Pendidikan Ganesha, 2024)
The underlying issue of this research is the need for innovative and effective learning media to support science education in elementary schools. This study aims to develop Tri Pramana-based digital learning media for the science subject to enhance the quality of teaching and learning processes. The research employed a development method using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The study involved 43 participants, including experts, teachers, and students. Data were analyzed qualitatively and quantitatively to assess the validity, practicality, and effectiveness of the developed learning media. The results showed that the Tri Pramana-oriented digital learning media has unique characteristics and was designed for Plants as a Source of Life on Earth topic, in 8 sessions, divided into two parts per session. The media validity was rated very high, with an average score of 0.98 (content), 0.94 (media), and 0.93 (language). The practicality of the media received an average score of 4.79 from teachers and 4.37 from students, both categorized as very practical. The effectiveness of the media, based on a trial involving 24 students, resulted in an average n-gain score of 0.68, categorized as moderate. Thus, the Tri Pramana-based digital learning media is deemed valid, practical, and moderately effective in supporting science education for elementary school students and has the potential for broader implementation.